Grapes - Creasy, G.L (CABI, 2014)
This book targets advanced plant science students with specific interest in viticulture and those who are producing grapes for the first time. We think it will be of interest to enthusiasts of the vine and its products who want to learn a bit more about how grapes are grown and a lot about the whys behind the methods. There are answers to many questions in the following chapters but, as always seems to be the case, the more you learn the more you discover that there is always more to learn! Grapes have so many uses and are so unique that no fruit can challenge their superiority. The production of grapes continues to grow: China now produces more table grapes than the next nine major producing countries combined. It seems inevitable that China will also dominate wine grape production at some point, which makes life in the industry terribly interesting and exciting! In fact, methods of grape production and how the fruit is utilized are changing rapidly. For example, the advent of year-round supplies of table grapes, facilitated through economic means of shipping between the northern and southern hemispheres, has bolstered demand for the product, leading to more innovation and investment in the industry and improvement in our ability to grow and market them. Grapes are being produced in many places where it was not considered possible before, largely due to advances in understanding of how the vine works, as well as to improvements in technology and management skills.